Laboratory evaluation on the characteristics and pollutant emissions of nanoclay and chemical warm mix asphalt modified binders - Abdullah, Mohd Ezree; Hainin, Mohd Rosli; Md. Yusoff, Nur Izzi; Zamhari, Kemas Ahmad; Hassan, Norhidayah (Elsevier Ltd., 2016)
This study was conducted to investigate the performance characteristics of nanoclay- and chemical warm-mix asphalt (WMA) additive-modified asphalt binders in terms of their chemical, morphology, rheological and surface energy properties in comparison to conventional asphalt binder. Both the nanoclay modified asphalt binder (NCMB B) and the chemical WMA additive modified asphalt binder (CWAA) were artificially aged under short-term and long-term aging conditions prior to evaluation. The chemical and morphological properties were measured with Fourier Transform Infrared (FTIR) spectroscopy and Field-Emission Scanning Electron Microscopy (FE-SEM) respectively. Rheological eval-uations were conducted to determine binder’s behavior under short-term aging in terms of frequency sweep, temperature sweep, and creep recovery tests by utilizing the dynamic shear rheometer (DSR) machine. Emission test was also conducted on the unmodified and modified WMA mixtures to estimate the gaseous pollutants emitted during their manufacture. FTIR spectroscopy results showed that the addition of WMA modifiers into asphalt binder could delay and weaken the oxidation reaction of the binder which in turn improved the aging process. However, the physical structure did not seem to show any changes after undergoing long term aging. The use of NCMB B 4% (by weight of asphalt binder) seemed to produce better resistance towards rutting when compared to CWAA 1%, 2% and 3% for unaged, and short- and long-term aging test conditions. The modified binders exhibit significantly higher surface energy and hence produced good adhesion between aggregates, which imply increased resistance toward moisture-induced damage. This study also revealed that the manufacture of WMA mixtures reduced up to 50% of the pollutants emitted during mixing in laboratory.